The Evaluation of Pavement Condition Assessment Methods for Road Assets in Coastal Areas - Teopilus, Clarence Deborah; Amrozi, Mukhammad Rizka Fahmi (Universitas Negeri Yogyakarta, 2023)
The Daendels road is a vital provincial road asset that facilitates the distribution of goods and services, enhances tourism access, and promotes socio-economic development in the southern region of Java Island. The deteriorated condition of the Daendels road pavement has the potential to escalate both the likelihood of accidents and vehicle operating costs. In Indonesia, road distress is measured using the Surface Distress Index (SDI), but certain types of distress are not yet incorporated into the calculation. Therefore, this study aims to identify the typical road distress in the coastal region and then to evaluate and compare several visual methods for evaluating the functional condition of road pavements, i.e., the SDI, Pavement Condition Index (PCI), and Pavement Surface Evaluation and Rating (PASER). Pavement conditions for Daendels Road have different analysis results depending on the method used. The average value of PCI is 50.5 (slightly damaged), the SDI is 164 (severely damaged), and the PASER is 4 (slightly damaged). The statistical analyses indicate that both the SDI-PCI and SDI-PASER methods have a very strong relationship. The SDI-PCI method has a higher correlation and coefficient of determination value (R= -0,929, R²= 0,8631) than SDI-PASER (R= -0,807, R²= 0,652). The PCI method is more applicable than the SDI dan PASER as it considers a wider range of pavement distress (19 categories) and more accurately represents the typical distress encountered on the South Coast of Java Island. The pavement condition of Daendels Road is classified as severely damaged with typical distress involving cracking (longitudinal, transversal, alligator, and blocks), patching, and pothole. Hence, a comprehensive plan for road maintenance was suggested, encompassing major rehabilitation using a hot mix asphalt overlay.